Marriage Postponement in the Mandailing Community: A Maqasid al-Shari'ah-Based Socio-Legal Analysis of Bujing-Bujing Tobang and Poso-Poso Tobang in Sibual-Buali Village - Sunnah warisah Hasibuan; Abd. Mukhsin (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2025)
This study examines the phenomenon of marriage postponement among bujing-bujing tobang (unmarried adult women) and poso-poso tobang (unmarried adult men) in Sibual-Buali Village, Padang Lawas, through the lens of maq??id al-shar??ah. Employing a qualitative design with an empirical-juridical approach, data were collected through semi-structured interviews with 12 informants across three age groups (25–27, 27–30, and 30+), alongside local customary leaders and religious scholars, complemented by library research on the Qur’an, Hadith, the Compilation of Islamic Law, and classical fiqh literature. Findings indicate that the dominant factors contributing to delayed marriage include economic instability, caregiving responsibilities, prior emotional experiences, and aspirations for education and career development. Analysis through the maq??id al-shar??ah framework reveals that these reasons align with the preservation of religion (?if? al-d?n), life (?if? al-nafs), intellect (?if? al-?aql), lineage (?if? al-nasl), and wealth (?if? al-m?l). Thus, marriage postponement is understood not merely as an individual preference but as a strategy to balance personal, familial, and spiritual obligations. The study recommends strengthening premarital education grounded in maq??id, refining marriage dispensation mechanisms, and applying the maq??id cum-mub?dalah approach. These findings provide actionable insights for policymakers, religious leaders, and scholars to integrate Islamic legal principles with contemporary social realities.